Peran Satuan Lalu Lintas Kepolisian Resor Kepahiang dalam Menertibkan Pelanggaran Lalu Lintas di Kalangan Pelajar Perspektif Fiqh Siyasah - Syailendra Hapis Matin; Imam Mahdi; Ismail Jalili (CV. Doki Course and Training, 2025)
This study aims to examine the role of the Kepahiang Resort Traffic Police in controlling traffic violations among students from the perspective of Fiqh Siyasah. The type of research used is field research with a qualitative approach, where data is obtained through observation and interviews to produce an in-depth description of the phenomenon being studied. The results of the study indicate that the role of the Kepahiang Resort Traffic Police in controlling traffic violations among students is carried out through two efforts, namely: (a) preventive efforts, in the form of prevention through socialization and education, and (b) repressive efforts, in the form of warnings, tickets, and advice to violators. In addition, the community also contributes to preventing violations through supervision and counseling in the surrounding environment. From the perspective of Fiqh Siyasah, these control efforts are in line with the principles of maslahah (benefit), 'adalah (justice), sadduz zara'i (prevention), and wilayah al-amr (government authority), so they have strong relevance in the context of law enforcement and social ethics.